The Future of eTextbooks (R&E-SOURCE, 2014)
Electronic versions of textbooks (eTextbooks) have recently become a hot topic in the educational community. The advent of tablet form PCs has further secured eTextbooks as one of the most frequently discussed issues among educators. How can they be compared to printed textbooks? On their web pages one of the leading publishers states: "An eTextbook is the complete contents of a printed textbook, delivered in electronic form over the Internet. … An eTextbook has the same content as a printed textbook, the same chapter divisions, and the same page numbering. …"We claim this is not the right way to go. A good eTextbook should be quite different from a printed textbook. What are the main characteristics of a good eTextbook, then? It should provide much more besides the obvious additions and improvements such as interactivity, usage of multimedia, and ease of navigation.As the need for individual approach towards each student is becoming more and more emphasized, one of the crucial changes we should expect and require is that an eTextbook should allow for customization and personalization. The customization should be achieved on different levels: be it technical (adaptation to different output devices where the eTextbook is to be used, tools used in examples and so on) or (more importantly) be it the adaptation of its content.But where should this customization occur? Should the publishers provide all the possible variations? Should the learners decide for themselves what is the most appropriate for them? We think that customization will be one of the most important parts of a teacher’s duties in the future. It is the teacher who is capable of making the proper combination of the teaching resources available, making it suitable for the particular pedagogical situation. Who if not the teacher is the most capable of assessing what is the preferred learning style of a specific learner, or which approach works best for each of his students. The teacher knows what tools are available, which technological skills his students possess … The personal characteristics of each teacher should not be neglected either; namely the way of teaching, personal beliefs, opinions regarding motivational approaches, etc. Therefore eTextbooks should be designed to be adaptable to the pedagogical situation and to the user, be it a learner or a teacher.Consequently, eTextbooks should be quite different from the printed editions. It should be a given that an eTextbook allows and enables uncomplicated customization and personalization. The talk will show some actual examples where some of the proposed ideas have already been implemented as well as a description of more practical ways showing what other concepts should look like.